Pendampingan Pendalaman Materi Matematika Untuk Anak-anak di Panti Asuhan Ash-Shohwah - Mayu Syahwela (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
Orphanage children who incidentally did not have parents or come from the poor make them did not have adequate learning facilities. It ultimately causes the orphans to have low learning outcomes or, in other words, no academic achievement at school. Most of them need more motivation to learn. The purpose of this service is to assist orphanage children, especially junior high school students, to deepen their understanding of math material, which is considered difficult, and to provide encouragement and motivation to study hard. The subjects of this activity were 12 junior high school students at the Pekanbaru Ash-Shohwah Orphanage. The results of this community service activity are: (1) getting a positive response from the management of the orphanage, (2) The children are satisfied with the mathematics learning assistance activities and hope that this activity will continue, (3) The children take part in the training enthusiastically and actively respond when the service team provides material.